Processing and recycling of aggregate residues after ore extraction for stabilization of mined areas - Andrea Jančíková; Karel Dvořák; Simona Ravaszová (Acta Polytechnica CTU Proceedings, 2024)
The article focuses on the treatment and recycling of aggregate. It also addresses the issue of treatments effects on mine tailings, fly ash and acid mine water on the measured parameters of concrete with load-bearing and backfilling paste with non-load-bearing function. Four different mixes were developed, and standard tests were performed on them. These mixtures were made with different types of mine tailing’s fillers with varying degrees of treatment. Mineralogical and chemical tests were carried out on the treated aggregates, with sieve analysis and their subsequent adjustment for suitable aggregate gradation curve in concrete. Strength and volumetric weight tests were carried out on hardened samples at 28, 56 and 90 days. The results of the determined functional specimens showed that it is possible to develop an almost completely waste-free technology using recycled aggregate and fly ash from the ore mining and energy industries and its subsequent processing and use for backfilling of mine deposits with load bearing and non-load bearing function concrete.